Produksi Film Dokumenter Sejarah Bandara Kemayoran Berjudul “Landasan Pacu Penuh Rindu” - Handi, Handi; Nurhablisyah, Nurhablisyah; Saptodewo, Febrianto (Cipta, 2024)
The Kemayoran Airport History Documentary entitled "Lost Railway Landing" aims to educate younger generations about the history of the international airport and preserve it. The research method used is a qualitative descriptive method aimed at finding knowledge or theory at a given time. With this method of research, the police are trying to present data related to Kemayoran airport from its construction to its use. The data collection is through literature studies, observations and interviews. The researchers make the results of interviews with the source as the main reference and the official website of the Kemayoran PPK as the secondary reference in the data collection. In the observation activities, the researchers conducted observations of remnants of Kemayoran Airport such as the former building of Kemuyoran Airport, the relief which is the VIP room, the ATC tower, until the runway on December 15, 2022. From the results of the observations, the researchers documented some of the places above in form and video. The sources contacted in this study are the PPK Humas Kemayoran, the historian of Jakarta, and Rumini Lailatul Anhar who is a citizen of Kemayor. The choice of documentary films as media because it can facilitate the explanation of history, as well as concrete the abstract. The design of this documentary, it is expected that the younger generation will be concerned about the history of the first international airport in Indonesia, and also to keep the remaining objects.